The Effectiveness of Kahoot in Improving Vocabulary: The Case of a Private University English Study Program - Udur Delima Sibatuara (Edukasi, 2021)
The purpose of this research was to find out the effectiveness of Kahoot application in improving the students’ English vocabulary. A study was conducted at the English Study Program students of Widya Dharma University Pontianak. The study adopted a mixed method by online using Google form and interviews directly by using zoom. The data were collected via questionnaire and interviews. The findings showed that the majority of the respondents who took part in the study mostly gave the positive responses which showed that Kahoot could help them greatly in improving their English learning vocabulary and could increase their motivation in gaining the knowledge and getting the new vocabularies.